Flexosomes for transdermal delivery of meloxicam: characterization and antiinflammatory activity. (17th February 2017) - Alomrani, Abdullah H.; Badran, Mohamed M.
Abstract: The study aims to investigate the impact of flexosomes (FLs) on transdermal delivery of meloxicam (MLX). FLs are composed of phospholipid, Tween 80, and ethanol which were prepared by film hydration method. The prepared FLs were characterized for particle size, zeta potential, and entrapment efficiency (EE). Ex vivo skin penetration studies were perfomed, and the best formulation was further evaluated using in vivo antiinflammatory activity test. FLs were in nano-size scale carring negative charge and observed high EE% and enhanced skin penetration of MLX compared to conventional liposomes (CLs). The best formula was FL4 which was composedof phospholipid (10%), Tween 80 (1.5%), and ethanol (40%). FL4 showed 143.4 nm vesicle size, 84% EE, and 31-fold ex vivo permeation enhancement through skin compared to CLs. The antiinflammatory activity of FL4 gel showed significant increase compared to control. This study observed the effectiveness of using FLs as carriers for transdermal delivery of MLX.